2023
DOI: 10.3390/w15061229
|View full text |Cite
|
Sign up to set email alerts
|

Review of Experimental Investigations of Dam-Break Flows over Fixed Bottom

Abstract: Laboratory experiments of dam-break flows are extensively used in investigations of geophysical flows involving flood waves, to provide insight into relevant aspects of the physics of the process and collect experimental data for validating numerical models. A dam-break flow is a typical example of a highly unsteady free surface flow with high reproducibility. Indeed, dam-break experiments can be repeated several times under the same test conditions obtaining large amounts of different types of data (possibly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 243 publications
0
11
0
Order By: Relevance
“…An extensive review of the state-of-the-art experimental investigations into dam-break flows was performed by Aureli et al (2023) [Contribution No. 4], limited to schematic test cases with fixed, non-erodible bottoms.…”
Section: New Laboratory Experiments and Test Cases For The Validation...mentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive review of the state-of-the-art experimental investigations into dam-break flows was performed by Aureli et al (2023) [Contribution No. 4], limited to schematic test cases with fixed, non-erodible bottoms.…”
Section: New Laboratory Experiments and Test Cases For The Validation...mentioning
confidence: 99%
“…The comprehensive review of experimental studies on dam-break flow reported by Aureli et al (2023) [Contribution No. 4] shows that in the past, an impressive number of experimental investigations were performed on this topic in a variety of test conditions, and many extensive and accurate datasets are available for the validation of dam-break numerical models.…”
Section: New Laboratory Experiments and Test Cases For The Validation...mentioning
confidence: 99%
“…Pereira (2017) also stated that hydraulic dam projects must be supported by studies/tests in a physical model, to carry out spillway capacity and flow energy dissipation tests (downstream erosive processes). In fact, physical models or reduced-scale models integrate the study of the flow with complex hydraulic structures (Motta, 1972;Marques & Unas, 2010;Aureli et al, 2021Aureli et al, , 2023Trautwein et al, 2022) mainly through cause-consequence scenarios of simulation. Several parameters are the main focus on the present state of art, including soil composition (Correia et al, 2018;Alzamily & Abed, 2022;Trautwein et al, 2022) and the understanding of the phenomenon of failure due to overtopping (inflow hydrograph).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the comparison of numerical results with measured data is crucial to assess the performance of the mathematical models. Both Chanson (2009) and Aureli et al (2023) have highlighted that apart from few exceptions (e.g. Aureli et al, 2015), detailed experimental data to fully assess the predictive capabilities of such models are not widely available, although such data are of utmost importance for numerical models validation (Aureli et al, 2015;Fang et al, 2022;Lara et al, 2012;Robertson et al, 2013;Stamataki et al, 2018;Wang et al, 2022;Wüthrich et al, 2018;Wúthrich et al2019).…”
Section: Introductionmentioning
confidence: 99%